2021
DOI: 10.1039/d0nr06464e
|View full text |Cite
|
Sign up to set email alerts
|

Stiffening of DU145 prostate cancer cells driven by actin filaments – microtubule crosstalk conferring resistance to microtubule-targeting drugs

Abstract: The crucial role of microtubules in the mitotic-related segregation of chromosomes makes them an excellent target for anticancer microtubule targeting drugs (MTDs) such as, e.g., vinflunine (VFL), colchicine (COL), and...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 87 publications
0
27
0
Order By: Relevance
“…Cell adhesion features already play an important role in various cancer treatments. Recently Kubiak et al 69 demonstrated that treatment with microtubule-targeting antimitotic drugs, such as vinca alkaloids and taxanes, can change actin cytoskeletal organization and cell mechanics, influencing drug resistance. Another study highlighted that integrin-mediated cell adhesion can have an impact on cancer drug sensitivity 70 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell adhesion features already play an important role in various cancer treatments. Recently Kubiak et al 69 demonstrated that treatment with microtubule-targeting antimitotic drugs, such as vinca alkaloids and taxanes, can change actin cytoskeletal organization and cell mechanics, influencing drug resistance. Another study highlighted that integrin-mediated cell adhesion can have an impact on cancer drug sensitivity 70 .…”
Section: Discussionmentioning
confidence: 99%
“…Since this is a short period of the cell cycle, the effect of a drug can be specific to the rapidly dividing tumor cells. Given the wide clinical use of vinca alkaloids and taxanes, currently, the microtubules represent the best target to date for cancer chemotherapy 69 . However, several clinical trials have proved integrins to be a promising therapeutic target to battle cancer cells, though no specific drug was found to be exceptionally effective 71 .…”
Section: Discussionmentioning
confidence: 99%
“…Immunofluorescent staining and confocal imaging were performed as described previously [ 50 ]. Briefly, microglial cells were seeded on glass coverslips in 24-well plates.…”
Section: Methodsmentioning
confidence: 99%
“…Initially, numerous experiments were focused on cancer biology, indicating the general conclusion that cancer cells are softer than their healthy counterparts, while for tissue, the opposite trend was observed [61,64]. Recently, AFM has been utilized to show that prostate cancer cells stiffen after treatment with chemotherapeutic agents such as cisplatin or microtubule interacting drugs [25,65]. Studies in this area reveal the significance of mechanical changes in cancer progression and provide a more in-depth explanation of pathogenesis as well as cellular response to treatment.…”
Section: Atomic Force Microscopymentioning
confidence: 99%